Is Islamic Monetary System Possible in Indonesia? Interrelation Study between BI 7 Days Reverse Repo Rate and Nisbah Rate - Aswad, A; Purnami, Juwita; Pratama, Andik; Fuzi, Amirah Bt Mohamad (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this study is to investigate the interrelationship between Bank Indonesia 7 Days Reverse Repo Rate (BI 7 DRRR) and Profit-Loss Sharing Rate (Nisbah Rate) in Islamic Sharia Banks (Bank Syariah Indonesia). Indonesia had been establishing conventional monetary system ever since and have yet to introduce Islamic approach to its monetary system. Now, in Islamic monetary perspective, interest rate doesn’t exist. Therefore, this research aimed to discover the possibility of Islamic approach in Indonesia’s monetary system, using Nisbah Rate launched by Islamic Sharia Banks as a substitution. The research was conducted using VAR (Vector Autoregression) to study the interrelationship between BI 7 Days Reverse Repo Rate and Nisbah Rate, using data obtained from Islamic Banking Statistics through Indonesia’s Financial Service Authority (OJK) monthly during 2021-2023. The result showed that both BI 7 Days Reverse Repo Rate and Nisbah Rate did cause impact on one another, and thus the possibility of establishing Islamic monetary system is not completely disregarded. This investigation contributes to the ongoing discourse surrounding the integration of Islamic financial principles into conventional monetary frameworks. By highlighting the reciprocal influence between conventional monetary policies and Islamic financial instruments, this study underscores the potential for a hybrid monetary system that accommodates Islamic principles within the Indonesian financial landscape.